Financing health care reforms: An overview of issues - Sharma, B.B.L. (1999)
Giving background on meaning and significance of health care in India, the author focuses on financing of health care reforms and discusses important situational points that have emerged in the context of liberalisation and the emphasis laid thereon in the Seventh and Eighth Plans. He then takes up several pertinent issues in health sector reforms having a bearing on our Constitutional provisions - like equity, accessibility of poor, efficiency in using resources and inadequacy of resources, gender bias, quality of health care, impact of liberalisation, etc., - and, while concluding, lists out the issues briefly for discussion on the theme. - Reproduced
Keywords: Health services